GENOTYPING OF CAMELS OF ALMATY REGION BY CSN2 DAIRY PRODUCTIVITY GENE (Experimental biology, 2021)
Camel milk is highly valued for its medicinal properties and high nutritional value. Camel milk and its products are easily digestible and therefore natural for the human body. Thus, the study of genetic diversity and selection of camels according to "preferred" genotypes is an important component of camel breeding in Kazakhstan.The β-casein protein, encoded by the CSN2 gene, makes up the largest part of the casein fraction of camel milk and is considered the main gene for the presence of alleles associated with different levels of expression. The g.2126A> G transition is located the TATA box region of the CSN2 gene promoter, with a presumed effect on the transcription factor binding activity, which determines the intensity of this gene expression. In the studied camel populations bred in the Almaty region, the total number of which is 53 animals, the frequency of the G allele was 0.36, while the frequency of the A allele was 0.64. Also, the Hardy-Weinberg equilibrium was equal to 0,006. The level of polymorphism showed a high result in populations 1, 2 and 4, amounting to 100%, while in the third population this indicator was 66.67%. For the studied populations, such statistical indicators were identified as the genotypes occurrence frequency, the observed and effective number of alleles, Nei's gene diversity etc., which give the population genetic characteristics of populations.